Elliptic partial differential equations and quasiconformal mappings in the plane [ - Astala, Kari , 1953-; Iwaniec, Tadeusz; Martin, Gaven (Princeton mathematical series, 2009)
Explores developments in the theory of planar quasiconformal mappings with a focus on the interactions with partial differential equations and nonlinear analysis.